Hepatitis B virus pre‐S region: Clinical implications and applications. (12th December 2020) - Sun, Huizhen; Chang, Le; Yan, Ying; Wang, Lunan
Summary: Hepatitis B virus (HBV) infection is a major threat to global public health, which can result in many acute and chronic liver diseases. HBV, a member of the family Hepadnaviridae, is a small enveloped DNA virus containing a circular genome of 3.2 kb. Located upstream of the S‐open‐reading frame of the HBV genome is the pre‐S region, which is vital to the viral life cycle. The pre‐S region has high variability and many mutations in the pre‐S region are associated with several liver diseases, such as fulminant hepatitis (FH), liver cirrhosis (LC), and hepatocellular carcinoma (HCC). In addition, the pre‐S region has been applied in the development of several pre‐S‐based materials and systems to prevent or treat HBV infection. In conclusion, the pre‐S region plays an essential role in the occurrence, diagnosis, and treatment of HBV‐related liver diseases, which may provide a novel perspective for the study of HBV infection and relevant diseases.